2002
DOI: 10.1113/jphysiol.2001.014894
|View full text |Cite
|
Sign up to set email alerts
|

Renomedullary and intestinal hyaluronan content during body water excess: a study in rats and gerbils

Abstract: Our previous studies in rats have suggested a role for renomedullary hyaluronan (HA) in water homeostasis. The gerbil is known for its unique ability to conserve water. In the present study renal papillary and intestinal HA were compared between groups of anaesthetized gerbils and rats before and after up to 6 h of i.v. water loading. Baseline papillary HA in gerbils was only 37 % of that in the rat. Water loading in rats increased the papillary HA content. Elevation was maximal (+27 %, P < 0.05) after 2 h of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Long-term treatment of Brattleboro rats with arginine-VP was associated with not only activation of lysosomal hyaluronate hydrolases (β-glucuronidase served as an indicator of their status), but also with accumulation of HA in the renal medullary interstitium. The content of HA in the renal interstitium depends on activity of its biosynthesis in the interstitial cells, hyperosmolarity served as a factor stimulating this process [4]. In the present study, the significant increase in osmolarity of released urine under the effect of VP (Table 1) was presumably directly related to the increase in osmotic gradient in the medulla.…”
Section: Resultsmentioning
confidence: 85%
“…Long-term treatment of Brattleboro rats with arginine-VP was associated with not only activation of lysosomal hyaluronate hydrolases (β-glucuronidase served as an indicator of their status), but also with accumulation of HA in the renal medullary interstitium. The content of HA in the renal interstitium depends on activity of its biosynthesis in the interstitial cells, hyperosmolarity served as a factor stimulating this process [4]. In the present study, the significant increase in osmolarity of released urine under the effect of VP (Table 1) was presumably directly related to the increase in osmotic gradient in the medulla.…”
Section: Resultsmentioning
confidence: 85%
“…This differential distribution of HA is important for urine concentration and dilution, and as early as 1958, Ginetzinsky found evidence that the HA-degrading enzyme hyaluronidase is excreted in the urine in larger amounts during dehydration and drops to zero during hydration (Ginetzinsky, 1958). We have previously demonstrated that during acute hydration, papillary HA increases (Goransson et al, 2002;Hansell et al, 2000;Rugheimer et al, 2008a): an effect that can attenuate water reabsorption by changing the permeability characteristics of the interstitium. In contrast, papillary HA content decreases during water deprivation, indicating that the mechanisms by which HA regulates renal fluid balance differ from those of vasopressin (AVP), one of the major hormones involved in the regulation of renal fluid balance.…”
Section: Introductionmentioning
confidence: 89%
“…HA is predominantly found in the interstitium of the renal inner papilla (medulla): in the renal cortex, the HA content is very low, only a few percent of that in the renal papilla (Wells et al,1990;Johnsson et al, 1996;Hansell et al, 2000;Goransson et al, 2002;Rugheimer et al, 2008a). This differential distribution of HA is important for urine concentration and dilution, and as early as 1958, Ginetzinsky found evidence that the HA-degrading enzyme hyaluronidase is excreted in the urine in larger amounts during dehydration and drops to zero during hydration (Ginetzinsky, 1958).…”
Section: Introductionmentioning
confidence: 95%
“…The high concentrations of HA in the kidney medulla support tubules and blood vessels and it is important for urine concentration [22]. HA also has a wondrous renal water handling capacity which is important for maintaining the concentration gradient and affects water transport in renal medulla [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies suggest that, this inhibition leads to RMIC apoptosis [15][16][17][18][19][20]. Furthermore, hyaluronan (HA) which is a negatively charged glycosaminoglycan (GAG) found in renal interstitium and in the synthesis by RMICs, may play an important role in maintaining of water homeostasis [21,22]. The high concentrations of HA in the kidney medulla support tubules and blood vessels and it is important for urine concentration [22].…”
Section: Introductionmentioning
confidence: 99%